Mitigating atherosclerosis: Integrating vaccines with gene targets - Alireza Haraj; Masoomeh Bakhshandeh; Nafiseh Shokri; Prand Shariat Rad; Ali Alyan; Zahra Chegini; Mohammad Ali Nazari; Seyed Parsa Seyedi Taji; Mohammad Najafi (American Heart Journal Plus)
The formation and progression of atherosclerotic plaques occur through cellular dysfunction and remodeling of the extracellular matrix in the sub-endothelial space of vessels. The immunity against specific antigens is suggested to mitigate the atherosclerosis process. Primarily, studies have suggested that certain antigens, such as ox-LDL, ApoB-100, CETP, PCSK9, HSP60, MHC-II-derived peptides, and interleukins, are involved in atherosclerosis. However, recognizing the intricate interplay between immune responses and the formation of arterial plaques is essential to optimize immunization against atherosclerosis. In this review, the roles of some genes were presented in triggering atherosclerotic plaque events. Furthermore, some immunization approaches are presented to target these genes. The studies suggested that vaccination against the progression of atherosclerosis is an essential and effective approach to reducing the high death rate in autoimmune diseases.